Renoprotective potential of exogen erythropoietin on experimental ruptured abdominal aortic aneurysm model: An animal study - Gokalp Altun; Yavuz Cakiroglu; Zerrin Pulathan; Esin Yulug; Ahmet Mentese (Iranian Journal of Basic Medical Sciences, 2020)
Objective(s): The aim of this study is to investigate the renoprotective effect of erythropoietin (EPO) on hypovolemic shock and ischemia/reperfusion (IR) injury on kidneys as end-organs in an experimentally-created ruptured abdominal aortic aneurysm (rAAA) model. Materials and Methods: Thirty anesthetized Sprague-Dawley male rats were randomized to sham ((Sh n:6) (Sh+EPO n:6)) or shock and I/R groups ((S/IR n:9) (S/IR+EPO n:9)). Additional surgical procedure except aortic exploration was not performed on Sh and Sh+EPO groups. 60 min of shock, 60 min of ischemia, and 120 min of reperfusion were applied on S/IR and S/IR+EPO groups. In the S/IR and S/IR+EPO groups, hemorrhagic shock, lower torso ischemia, and reperfusion were created. At the end of the shock period, saline solutions were separately and equally administered to Sh and S/IR groups, whereas 2000 U/kg EPO was intraperitoneally administered to Sh+EPO and S/IR+EPO groups. At the end of the experimental study, some biochemical and histological parameters were studied in serum and kidney tissues. Results: Biochemical parameters were all significantly increased in the S/IR group compared with the Sh group. These parameters were not statistically significantly different between S/IR+EPO and Sh+EPO groups. In histopathologic examination, EPO prevented high-grade injury. Conclusion: Our data indicate that EPO may have a renoprotective effect and reduce the systemic inflammatory response that resulted from shock and I/R in an experimental model of rAAA.